Navigating in a sea of uncertainty : an emerging economy multinational - Salwan, Prashant (SAGE Knowledge. Cases., 2015)
This case study concerns an emerging economy multinational Bharat Forge Ltd. (BFL). BFL was founded in 1961 and became the world's largest forging company by 2008-09. BFL manufactured forgings for several industries around the world including the automotive, power, oil and gas, marine and aerospace, and railways industries. The external environment became increasingly dynamic and uncertain from 1991 onwards after Indian market liberalisation. This liberalisation however gave BFL the opportunity to absorb new technologies as well as to build new relations with international players. From 2004 onwards BFL focused on its international business strategy. Due to the global recession's impact on the US, Europe, Japan, China and of course India in 2008-09, BFL's production capacity fell to 20%. This greatly reduced the company's financial standing. Mr Baba Kalyani (BFL's CMD) had to decide on ways to survive the uncertainties and seek a more sustainable competitive advantage moving forward.